Students' interests in technical and vocational education and training (TVET) program: a systematic review - Azeem, Nazia; Omar, Muhd Khaizer (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Technical and vocational education and training program is also known as TVET has been widely acknowledged as one of the most important subjects in the educational system. The purpose of this study is to examine the existing literature specifically from the lenses of students’ perspectives on their interests and behavior towards TVET as their chosen subject matter for their educational journey. The authors reviewed 15 articles within the 2008-2018 publication years. The source of databases was derived from the ERIC database and peer-reviewed as well as indexed journal accessible online were employed to develop this article. This article focuses on the contents, arguments, terminologies, methodologies, and findings of the research derived from the selected articles. The findings of this article promulgate some important implications for practitioners and researchers who are researching within the same research area.